Antimicrobial meroterpenoids from the endophytic fungus Penicillium sp. T2-8 associated with Gastrodia elata. (December 2016) - Duan, Rongting; Zhou, Hao; Yang, Yabin; Li, Hongtao; Dong, Jianwei; Li, Xiaozhan; Chen, Guangyi; Zhao, Lixing; Ding, Zhongtao
Graphical abstract: Highlights: Preaustinoid D (1 ) was an analogue of austin with the opened A ring. Dihydroxyneogrifolic acid (2 ), a new neogrifolin derivative, was isolated from microorganism. The meroterpenoids exhibited obvious antimicrobial activities. Abstract: A new meroterpenoid preaustinoid D (1 ) and a new neogrifolin derivative dihydroxyneogrifolic acid (2 ), together with other five previously reported meroterpenoids (3 -7 ) were isolated from the endophytic fungus Penicillium sp. T2-8 associated with Gastrodia elata . The structures were elucidated on the basis of spectroscopic data analyses. It was the first time that neogrifolin and its derivatives were isolated from microorganism. Some of these meroterpenoids exhibited obvious antimicrobial activities in the microdilution antimicrobial assays.